The Role of Language Communication with The Society and Culture: Array - MZ, Zainab (Universitas Harapan Medan, 2021)
This research discusses the relationship of language communication with society and culture. Bahasa Indonesia as a language of unity is used in activities to communicate by the wearer community from various tribes and regions. As an effective means of communication the Bahasa Indonesia has an important role in developing and launching various aspects of life and culture. This research uses the method of literature writing (library research). To know the language activities of a person does not merely use the language as communication, but rather describes other aspects outside the linguistic aspect. These aspects may affect the style, dialect, variety, form language it uses and show the user a separate language item that is closely related to the language (social class, ethnic group, nationality and geographical location of the linguist). Linguistically different but still not mentioned as a different language. Such language differences are called language variations.